2015
DOI: 10.1007/s40195-015-0318-5
|View full text |Cite
|
Sign up to set email alerts
|

Laves Phase Formation and Its Effect on Mechanical Properties in P91 Steel

Abstract: Effect of Laves phase formation on mechanical properties in a pressurized T-junction of P91 steel pipe at 849 K for 58,000 h with 25.65 MPa vapor pressure was studied. Thermodynamic calculations had been performed by using the software Thermo-Calc to study the phase at equilibrium state. Counter plot of von Mises stress in the pipe during service life was calculated by finite element analysis to study the effect of the operated stress distribution on the evolution of Laves phase. The change in the microstructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
(35 reference statements)
0
5
0
1
Order By: Relevance
“…The effect of Laves phase on the mechanical properties, beneficial or detrimental, mainly depends on the volume fraction and mean size of Laves phase in the RHEAs. With increasing mean size and volume fraction of Laves phase, crack initiation and crack growth would rapidly increase [48]. In this study, small cracks can be observed around the indentations employed for the 1200 °C homogenised Ti-V-Cr-Nb-Ta sample, but not for the 800 °C homogenised Ti-V-Cr5-Nb-Ta sample, Fig.…”
Section: C15 Laves Phasementioning
confidence: 49%
“…The effect of Laves phase on the mechanical properties, beneficial or detrimental, mainly depends on the volume fraction and mean size of Laves phase in the RHEAs. With increasing mean size and volume fraction of Laves phase, crack initiation and crack growth would rapidly increase [48]. In this study, small cracks can be observed around the indentations employed for the 1200 °C homogenised Ti-V-Cr-Nb-Ta sample, but not for the 800 °C homogenised Ti-V-Cr5-Nb-Ta sample, Fig.…”
Section: C15 Laves Phasementioning
confidence: 49%
“…These converse effects of the Cr additions on strength/ductility were attributed by the authors to the formation of the Laves phase that is expected from the thermodynamic point of view [6,7]. Several studies have clearly proven that the Laves phase is inherently brittle at lower temperatures [8,9]. In a very recent study, Senkov et al investigated the microstructure and mechanical properties of the alloy Al-Mo 0.5 -Nb-Ta 0.5 -Ti-Zr [10].…”
Section: Introductionmentioning
confidence: 89%
“…Most of the factors influencing precipitation strengthening depend on the particle size obtained during the nucleation and growth stages [90]. On the other hand, during exposure to high temperatures under constant load, high chromium ferritic steels have been found to have high intermetallic stability, unlike the rapid growth observed in 9%-12%Cr ferritic/martensitic steels.…”
Section: ¯( )mentioning
confidence: 99%
“…On the other hand, during exposure to high temperatures under constant load, high chromium ferritic steels have been found to have high intermetallic stability, unlike the rapid growth observed in 9%-12%Cr ferritic/martensitic steels. In both cases, the creep conditions tend to increase the diffusion of the elements that form Laves-phase, affecting the growth and coarsening of the particulate, decreasing the anchoring on the high-angle grain boundaries [90,91]. Initially, the fine Laves-phase adopt the shape of a needle, maintaining a semi-coherent (or coherent) interface with the matrix.…”
Section: ¯( )mentioning
confidence: 99%